Maternal inflammatory, lipid and metabolic markers and associations with birth and breastfeeding outcomes - Christensen, Sophie Hilario; Rom, Ane Lilleøre; Greve, Tine; Lewis, Jack Ivor; Frøkiær, Hanne; Allen, Lindsay H.; Mølgaard, Christian; Renault, Kristina Martha; Michaelsen, Kim F. (Frontiers in Nutrition, 2023)
Background: Conditions in utero influence intrauterine and postnatal infant growth and a few studies indicate that maternal inflammation and insulin resistance might affect pregnancy and breastfeeding outcomes. Furthermore, hormones in human milk (HM) may influence infant appetite-regulation and thereby milk intake, but the associations are less understood. Objective: 1) To investigate associations between maternal inflammatory, lipid and metabolic markers and pregnancy and breastfeeding outcomes, and 2) to assess predictors of maternal inflammatory, lipid and metabolic markers in pregnancy. Methods: Seventy-one mother-infant dyads participating in the Mothers, Infants and Lactation Quality (MILQ) study were included in the present study. Fasting blood samples were collected around 28th gestational week, and HM samples at three time points from 1.0-8.5 months, where milk intake was assessed using 24-hour test weighing. Maternal plasma inflammatory, lipid and metabolic markers included high-sensitive C-reactive protein (hs-CRP), tumor-necrosis factor-α (TNFα), interferon-γ (IFNγ), Interleukin (IL)-6, IL-8, high-, low-, and very-low-density lipoprotein (HDL, LDL, VLDL), total-cholesterol, triglycerides, leptin, adiponectin, insulin, C-peptide, the homeostasis model assessment of insulin resistance (HOMA-IR) and glucose concentration at t=120 minutes following an oral glucose tolerance test. Of these, TNFα, IFNγ, IL-6, IL-8, leptin, adiponectin and insulin were also measured in HM samples. Results: HDL in pregnancy was inversely associated with gestational age (GA) at birth and GA-adjusted birthweight z-score, whereas triglycerides and glucose(t=120) were positively associated with GA-adjusted birthweight z-score. Higher hs-CRP, VLDL and triglycerides were associated with a higher placental weight. Furthermore, higher HDL, insulin, leptin and HOMA-IR were associated with longer duration of exclusive breastfeeding (EBF). Higher pre-pregnancy BMI was the main predictor of higher levels of hs-CRP, log-TNFα, leptin, insulin, C-peptide and HOMA-IR. Conclusion: Maternal lipid and metabolic markers influenced birthweight z-score and placental weight as well as duration of EBF. Furthermore, pre-pregnancy BMI and maternal age predicted levels of several inflammatory and metabolic markers during pregnancy. Our findings indicate that maternal lipid and metabolic profiles in pregnancy may influence fetal growth and breastfeeding, possibly explained by overweight and/or higher placental weight.